Health system costs and systemic treatment patterns by disease stage for 8577 people diagnosed with melanoma in New South Wales, Australia 2006–2019 - David E. Goldsbury; Anne E. Cust; Caroline Watts; Alison Pearce; Philip Haywood; Louisa G. Collins; Preston Ngo; Kirstie McLoughlin; Michael Caruana; Karen Canfell; Julia Steinberg; Marianne F. Weber (PLoS ONE, 2026)
Background Australia has the highest melanoma rates in the world. Melanoma is the third most common invasive cancer in Australia, and the number of in situ diagnoses is rapidly increasing. Treatment for non-localised stage melanoma is evolving, improving survival and increasing costs. We describe the costs and selected treatments by stage of disease for people diagnosed with melanoma in a large Australian cohort study. Methods Questionnaire data for participants in the Australian 45 and Up Study (n = 267,357 recruited 2005–2009) were linked with cancer registrations, hospital records and Medicare claims records. To estimate the government healthcare costs attributable to melanoma, total costs for each participant with melanoma were compared to costs for matched cancer-free controls. Multivariable gamma regression was used to estimate factors associated with costs. We also examined the distribution of melanoma treatments by disease stage. Results There were 8577 participants diagnosed with melanoma after recruitment (5026 in situ and 3551 invasive; median age 69 years at diagnosis). The mean excess per-person costs in the first year after diagnosis (‘initial phase’) ranged from $2794 Australian dollars (US$1825) for in situ melanoma to $70,070 for distant metastases. The corresponding mean annual costs in the continuing care phase were $1222 and $38,470, respectively. Of 195 participants with regional/metastatic melanoma diagnosed 2014–2019, 80 (41%) had a record of immunotherapy/targeted therapy and their unadjusted per-person costs were approximately $60,000 higher annually than the 115 participants without these treatments. Conclusions Health system costs increased greatly with advancing melanoma stage, with higher costs linked to uptake of new immunotherapies/targeted therapies. Cost savings could arise from initiatives that detect and successfully treat melanomas at earlier stages, or prevent melanomas entirely.